Character Education Through Local Wisdom Culture at MA Al Iman Adiwerna - Awaludin, Aziz; Jannah, Roikhatul; Khoerul Anam, Muhammad; Mahdiyah, Nishrina; Jamal Maulidhana, Abdul; Apriyani, Afni; Ayu Lestari, Diah (International Journal on Education Issues, 2025)
Purpose - This research was pointed to knowing the usage of character instruction through school culture. with a center on devout character, teach character and free character. This ponder utilized a subjective approach with the plan of the ponder of multi case (multycase studies). The information collection strategy of this inquire about were the perception, interviews, and documentation. The comes about of the ponder appeared that the usage of character instruction through school culture centered on devout character, teach, and freedom. Each character is gotten through. Design/Methodology/Approach - This research employs a field research approach with observational methods. The purpose of this method is to describe, identify, and understand situations or events as they naturally occur without manipulating or altering the observed variables. Findings - The results of this research are based on an analysis focused on the practice of moral and religious character at Madrasah Aliyah Al-Iman. The practice of religious character values through the culture of Madrasah Aliyah Al-Iman can be observed in daily activities, religious events, and exemplary behavior. Originality/Value – Daily activities such as congregational prayers and tadarus should be carried out consistently so that character values can be firmly ingrained in students. Unstable implementation of this activity can reduce its positive impact on student character development..